WORKING IN SERVICES ENTERPRISES SPECIAL FEATURES OF THE SYSTEM - Ziyovaddinovna, Djalolova Saodat; Eshnazarovich, Ernazarov Ortiq (International Journal of Psychosocial Rehabilitation, 2020)
The article examines several features of the remuneration system in the service sector and recommended that an appropriate incentive system be established.